PRACTICALITY OF ELECTRONIC LEARNING MATERIALS ENERGY AND MOMENTUM INTEGRATED STEM WITH FLIP PDF PROFESSIONAL TO IMPROVE HIGH SCHOOL STUDENT’S LEARNING OUTCOMES - Yuni Fitria; - Asrizal; - Murtiani; - Gusnedi (PILLAR OF PHYSICS EDUCATION, 2022)
Industrial revolution 4.0 has made a big contribution to life. The era of the industrial revolution 4.0 requires human resources that can compete in the global economy. STEM education plays an important role in increasing student creativity so that they can compete in the future. However, in reality, activities that support student creativity in learning have not been carried out properly. The learning materials used were still limited and have not integrated STEM optimally, and student learning outcomes were still in the sufficient category. The solution to overcome these problems is to develop electronic learning materials that integrated STEM to improve student learning outcomes. The research method in this research was Research and Development (R & D). This study aimed to determine the practicality of STEM integrated electronic learning materials. The practicality of STEM integrated electronic learning materials obtained in this study was based on four practical components, namely ease of use, the attractiveness of presentation, clarity of the material, and benefits of learning materials. The average value of practicality of STEM integrated energy and momentum electronic learning materials using professional flip pdf was 85.79 which was categorized as the “very good” category. So it can be concluded that STEM integrated electronic materials can be used in physics learning to improve the learning outcomes of grade X students.